Infertilitas Pada Pasangan Suami Istri di Kota Makassar - Ikhsan, Muhamad; Multazam, Andi Muhammad; Asrina, Andi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
The problem of infertility is still a health problem that has not been fully resolved due to various factors that cause this infertility. Infertility also affects the psychology of a married couple where they do not have offspring, which is one of the goals of marriage. So this study aims to study and analyze infertility in infertile couples in the city of Makassar. This research was conducted in the city of Makassar and the time of the study will be held from February to April 2018, during which time primary data collection will be carried out. This study uses qualitative research methods with a phenomenological approach. The informants of this study were four pairs of ordinary informants and / or supporters and one key informant. Data collection techniques using in-depth interviews, observation and documentation. Data analysis using component analysis (content). The results of the study showed that sexual activity, sexual arousal, or interest in sexual intercourse by a married couple during the infertility period did not experience interference and anxiety in infertile couples seems to know at the outset that they have infertility. The conclusion of this study was that the impact of infertility on sexuality experienced was not felt, sexual relations between married couples did not experience problems. As well as the impact of infertility on anxiety in infertile couples appear at the beginning to know that they are infertile, those feelings arise because of the desire to have offspring.